PELAKSANAAN SUPERVISI AKADEMIK KEPALA SEKOLAH BAGI GURU PENDIDIKAN AGAMA ISLAM DI SMA NEGERI 1 PEUDAWA - Muhammad Fauzi (Conciencia, 2016)
The purpose of the research Implementation of academic supervision, and follow-up of the academic supervision of the principal of Islamic Education teachers (PAI) in SMA Negeri 1 Peudawa of East Aceh district. This research was a qualitative descriptive study. This study used a purposive sample. The data collection used the methods: First, interviews by using a structured interview instrument to the principal and three teachers of PAI who were become informants in this study. Second, the observation by the way of observing directly implementation of the academic supervision of the principal toward teachers of Islamic Education (PAI) in SMA Negeri 1 Peudawa East Aceh district in the implementation of the learning process. Third, documentation by data collection through written relics, archives, letters, photographs, online data, and books about the academic supervision. The results showed that: First, principal in SMAN 1 Peudawa East Aceh district had implemented the planning of the academic supervision as making programs, schedules and making instrument of academic supervision. Second, principal in SMAN 1 Peudawa East Aceh district had implemented the academic supervision by observation techniques to three teachers of PAI. Third, principal in SMAN 1 Peudawa East Aceh district had implemented a follow-up to the academic supervision of three teachers of PAI in the form of a meeting feedback (feedback) and had implemented the coaching to three teachers of PAI.